Vaccination Against COVID-19 in a Network of Hemodialysis Units in Portugal: A Promising Experience - João Fazendeiro Matos (Acta Médica Portuguesa, 2022)
Introduction: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) responsible for coronavirus disease 2019 (COVID-19) seriously affected Portugal, particularly in the elderly population with a high number of comorbidities, including patients with chronic kidney disease in stage 5 (CKD-5D) undergoing a regular dialysis program. The aims of this study were to identify the impact of vaccination on the incidence of new daily cases and mortality in the CKD-5D population. Material and Methods: Prospective, observational study, involving patients with CKD-5D from 38 NephroCare clinics, Portugal. Daily SARS-CoV-2 infections and mortality among these patients was compared with the incidence in the general population. Three periods were analysed: before vaccination, during the vaccination process, and a third period after complete vaccination with the Pfizer-BioNTech’ Comirnaty® vaccine. The primary outcome was infection by the SARS-CoV-2 virus and the secondary outcome was death associated with the infection. Results: A total of 4617 patients (average of 69.37 years of age) were analysed. During the first period, there was a significantly higher COVID-19 incidence of 14.9% in patients with CKD-5D compared with the general population (7.9%; p < 0.001). During the fifteen days after the complete vaccination, results reverted to a significant decrease in COVID-19 cases was observed (p < 0.001). The mortality rate among CKD-5D was significantly higher than in the general population (p < 0.001). Discussion: A high incidence rate of infection was observed in CKD-5D patients, probably due to several factors such as advanced age, number of comorbidities, inability to remain in confinement, among others. After vaccination there was a significant reduction of new cases. Conclusion: Vaccination significantly reduced SARS-CoV-2 infection in patients with CKD-5D.